The Bland or the Bountiful? Notes on Australian Dining Between the Wars - van Reyk, Paul (Petits Propos Culinaires, 2016)
Looks at what people now remember as "plain" cooking in Australia between the wars, surveying popular cookbooks of the time. Those cookbooks would have mostly been used by White Australians even though three ethnic groups – Germans, Chinese and Italians – had formed significant immigrant populations in Australia but this time. Of these, it seems only Italian foodways had some influence.